Design principles for utility-driven services and cloud-based computing modelling for the Internet of Things. (1st January 2014) - Soldatos, John; Kefalakis, Nikos; Serrano, Martin; Hauswirth, Manfred
By following an analysis of the state of the art in the convergence of cloud computing and the Internet of Things (IoT), this paper presents design principles for the IoT in cloud environments. A framework for on-demand establishment of IoT services based on the automated formulation of societies of internet-connected objects is described and the interactions between architecture modules are explained in detail to validate this approach. The main building blocks of the functional framework and its operational components follow the utility-driven cloud-based computing model. The framework leverages well-known technologies (i.e. linked sensor data) and standards (notably the W3C semantic sensor networks ontology). Finally, an example for service formulation and delivery of services for a smart campus scenario is provided and discussed. This paper also introduces some experiment results using the utility-driven service formulation model for mobile applications.